Different faces of inequality across Asia: Decomposition of income gaps across demographic Groups - Vladimir Hlasny (Asian Development Bank Institute (ADBI), 2017)
Substantial evidence exists that economic inequality in Asia has been growing, but the dimensions of this inequality and its growth are far less clear. This paper evaluates inequality in household incomes per capita across various demographic groups in income surveys from six middle- and high-income countries across Asia: the People's Republic of China (PRC) (2002); India (2004); Japan (2008); Republic of Korea (2006); the Russian Federation (2004, 2007, and 2010); and Taipei,China (2005, 2007, 2010). These surveys, made available by Luxembourg Income Study, are unique in that they are harmonized across countries and time, cover even Asia's developing countries, and encompass over 130,000 household records. This study describes patterns in overall inequality, inequality in various quantiles of national income distributions, and income differentials across various demographic groups. Income gaps due to households' rural/urban residence, administrative region, education and employment status, and gender are assessed at various income quantiles using unconditional quantile regressions, and are decomposed into parts due to differentials in household endowments and parts due to differentials in returns to those endowments. Japan; Taipei,China; and Republic of Korea have very low degrees of overall income inequality by world standards, while India and the PRC have high levels. The Russian Federation has a medium degree of inequality, sluggishly improving over time. Rural/urban income gaps are evident across all evaluated countries, but they are particularly high in the PRC, India, and the Russian Federation, accounting for a large share of overall inequality. The rural/urban gap has been falling in the Russian Federation and Taipei,China. Inequality between disadvantaged and advantaged regions is high in the PRC and India, followed by the Taipei,China. Over time this gap stagnated in Taipei,China and further deepened in the Russian Federation, disagreeing with claims of market integration and convergence in recent Russian Federation reports. Education gap is an important component in overall inequality across most countries, especially in the PRC and India. Employment gap is notably large among poor households in the Republic of Korea and Taipei,China, due to differential returns to household endowments, suggesting that non-employed individuals have similar skills as their employed counterparts, but markets and the welfare state do not bestow them with adequate compensation for their skills. Gender gaps are surprisingly small across the six countries - women appear to have a similar distribution of endowments as men, and returns to them are not significantly lower. Polarization arises in the evaluated societies whereby a small group of households come in possession of large stocks of endowments and concentrate in cities and advantaged regions to receive high returns on their endowments. The rest of the populations, notably in India, lack resources to invest in market-valued characteristics to lift themselves up. Overall, education and the return to it, geographic location, and household composition play important roles in driving economic inequality - and suggest viable ways to control it - across demographic groups.
Keywords: D31; D63; N35; 330; Economics; China; People's Republic of; India; Japan; Korea; Republic of Taipei; China